(untitled) (The Research of Medical Science Review, 2025)
Background: Self-esteem, an individual's subjective evaluation of their own worth, significantly influences mental health, motivation, and overall quality of life. Both excessively high and low self-esteem can be detrimental. This study aimed to assess the level of self-esteem among nurses and nursing interns working in the critical care area of teaching Hospital of Swabi, KPK, and to explore potential work-related factors influencing their self-perception.Methodology: A descriptive cross-sectional study design was employed to determine the self-esteem levels of nurses and nursing interns at teaching hospital of Swabi. Convenient sampling was used to recruit 59 participants who completed the Rosenberg Self-Esteem Scale, a 10-item questionnaire assessing positive and negative self-perceptions. Data analysis involved calculating frequencies, percentages, and identifying associations between self-esteem levels and work-related factors.Results: The study revealed that the majority of participants (75.99%) exhibited high self-esteem, while 20% showed normal self-esteem levels. A smaller proportion (3.66%) indicated low self-esteem. Work shift patterns and ward assignments, particularly the emergency department, were identified as factors potentially affecting self-esteem levels.Conclusion: The findings suggest that most nurses and nursing interns at BKMC Swabi have a positive perception of their self-worth. However, the identification of work shift patterns and ward assignments as influencing factors underscores the need for workplace interventions and support mechanisms to foster and maintain self-confidence among nursing professionals in this critical care setting